Role of electrochemical process parameters on the electrodeposition of silicon from 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ionic liquid. (1st March 2018) - Thomas, Shibin; Kowalski, Damian; Molinari, Michaël; Mallet, Jeremy
Abstract: The electrodeposition from Room Temperature Ionic Liquids (RTILs) has recently emerged as a low cost technique for the growth of group IV thin films or nanostructures giving some promising alternative to classical physical vapour or chemical vapour deposition techniques. As a relatively new field of research, only few studies exist describing the growth mechanism of electrodeposition from RTILs, especially for Si films. In the present work, Cyclic Voltammetry (CV), Electrochemical Quartz Crystal Microbalance (EQCM) and potentiostatic electrodeposition techniques have been used to study the role of the applied potential, the concentration of electroactive species, the temperature, and the use of organic additive on the electrodeposition of Si from 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ionic liquid. The demonstrated investigation of the influence of these parameters on the purity and morphological features gives a better control over the growth of Si thin films and optimizes the technique to grow Si with structural properties suitable for specific applications.